2017
DOI: 10.1007/s11845-017-1596-x
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of lncRNA HOTAIR rs12826786 C>T polymorphism and gastric cancer susceptibility in a Turkish population: lack of any association in a hospital-based case–control study

Abstract: Our results demonstrate that the HOTAIR rs12826786 C>T polymorphism has not been in any major role in genetic susceptibility to gastric carcinogenesis, at least in the population studied here. Independent studies are needed to validate our findings in a larger series, as well as in patients of different ethnic origins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 22 publications
0
8
1
Order By: Relevance
“…However, the results of these studies are inconsistent. For example, a previous study report that the T allele of rs12826786 increased the risk of developing adenocarcinoma of the gastric cardia in a Chinese population [28]; however, among the Turkish population, researchers found that the same variant (HOTAIR rs12826786 C>T polymorphism) was not associated with genetic susceptibility to gastric cancer [29]. In our study, we found that rs920778 was associated with the development of hepatocellular carcinoma.…”
Section: Discussioncontrasting
confidence: 46%
“…However, the results of these studies are inconsistent. For example, a previous study report that the T allele of rs12826786 increased the risk of developing adenocarcinoma of the gastric cardia in a Chinese population [28]; however, among the Turkish population, researchers found that the same variant (HOTAIR rs12826786 C>T polymorphism) was not associated with genetic susceptibility to gastric cancer [29]. In our study, we found that rs920778 was associated with the development of hepatocellular carcinoma.…”
Section: Discussioncontrasting
confidence: 46%
“…15,16 Several studies investigated the impact of HOTAIR gene polymorphisms on the incidence risk of various cancers including BC, gastric cancer, prostate cancer, and ovarian cancer. [17][18][19][20][21][22][23][24][25] However, the data from these studies remain controversial and inconclusive. Furthermore, few studies have been conducted regarding the association of HOTAIR gene polymorphisms on BC risk.…”
Section: Introductionmentioning
confidence: 99%
“…The functional role of long non-coding RNA (lncRNAs) in the biological activity of malignant tumor has been widely investigated [3] , [4] . By regulating the expression of target gene through different mechanisms, lncRNAs have been reported to be associated the growth and metastasis of a variety of cancer [5] , [6] , [7] . Aberrant upregulation of oncogenic lncRNA TUG1 was observed in B-cell malignancies, bladder cancer, hepatocellular carcinoma and OS [8] .…”
Section: Introductionmentioning
confidence: 99%